Diagnostic challenges of brucellosis in humans and livestock in Tanzania: A thematic review - Mengele, I.J.; Shirima, G.M.; Bronsvoort, B.M.; Hernandez-Castro, L.E.; Cook, Elizabeth A.J. (CAB International, 2023)
Brucellosis is an endemic bacterial zoonosis in Tanzania, and is among the most prioritized zoonotic diseases in the country. Brucellosis affects public health and livestock production in developing countries. Most human and livestock cases are not detected by the existing surveillance systems resulting in significant underestimation of the disease burden, and poor management of human cases by using nonspecific antibiotics may potentially contribute to antimicrobial resistance. To quantify the factors related to underreporting and those associated with the challenges in the diagnosis of brucellosis in Tanzania, search terms including “Brucella” “diagnosis” and “challenges” were used to query in Google search engine and publisher databases such as MEDLINE, PUBMED, NCBI, Springer, Hindawi, and Elsevier. The search parameters were limited to publications between 1995 and 2020. The searches returned 319 publications and grey articles which were screened and 57 were eligible for inclusion in this study. Four main areas were identified that cause underreporting of brucellosis and hinder brucellosis diagnosis: (1) inadequate knowledge of brucellosis among stakeholders in the livestock value chain, (2) limited diagnostic capacity for brucellosis due to unawareness of diagnostic tests and lack of epidemiological background of brucellosis among human and livestock health service workers (3) challenges associated with diagnostic tests, which include unreliable availability of diagnostic tests and unskilled workers, and (4) the uneven distribution of brucellosis surveillance studies in the country. This study suggests that there is a need for (1) training on public health education and brucellosis awareness among stakeholders in the livestock value chain; (2) providing scheduled continuing professional education with regard to brucellosis and other zoonotic diseases to health and livestock workers; (3) future brucellosis surveillance studies must focus on unrepresented regions; and (4) lastly, we recommend that the rose Bengal plate test (RBPT) and competitive enzyme-linked immunosorbent assay (cELISA) should be considered in brucellosis diagnostic schemes as a complementary tool to hasten the implementation of an ongoing national strategy for the prevention and control of brucellosis in humans and livestock in Tanzania. We suggest that these recommendations be considered for inclusion in the national strategy for brucellosis control in Tanzania.